High-performance polyacrylonitrile-based carbon fiber and preparation method thereof

By adding plasticizers and pre-oxidizing and carbonizing during the preparation of polyacrylonitrile fibers, the problem of insufficient tensile strength of carbon fibers is solved, significantly improving the mechanical properties and structural orientation of the fibers, and expanding its application scope.

CN119287559AActive Publication Date: 2025-01-10SHANDONG UNIV

Patent Information

Application Number
CN202411552490.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-10
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The mechanical properties of existing carbon fibers, especially tensile strength, have failed to reach theoretical values, limiting their wider commercial applications.

Method used

During the preparation of polyacrylonitrile fibers, special plasticizers such as diphenyl phthalate, bisphenol A-bis(diphenyl)phosphate or resorcinol bis(diphenyl)phosphate are added. Improve the drawability of the fibers and improve the structure and performance of carbon fibers through preoxidation and carbonization.

Benefits of technology

It significantly improves the tensile strength and modulus of carbon fibers, improves the structural orientation and graphitization of fibers, and expands its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287559A_ABST
    Figure CN119287559A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance polyacrylonitrile-based carbon fiber and a preparation method thereof, and the preparation method comprises the following steps: proportionally mixing polyacrylonitrile, a solvent and a plasticizer, heating and stirring to obtain a uniform spinning solution; the plasticizer is diphenyl phthalate, bisphenol A-bis (diphenyl) phosphate ester or resorcinol bis (diphenyl) phosphate ester; spinning the spinning solution to prepare a polyacrylonitrile fiber precursor; carrying out hot drawing treatment on the polyacrylonitrile fiber precursor, and then carrying out pre-oxidation and carbonization treatment to obtain polyacrylonitrile-based carbon fibers; the pre-oxidation temperature ranges from 200 DEG C to 300 DEG C, and the pre-oxidation time ranges from 80 min to 160 min. The preparation method of the carbon fiber can effectively improve the spinnability and the draftability of the PAN fiber, and can promote the crystallinity and the graphitization degree of the carbon fiber to be improved, so that the mechanical property of the fiber is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of polyacrylonitrile-based carbon fibers, and relates to a high-performance polyacrylonitrile-based carbon fiber and a preparation method thereof. In the preparation process of the polyacrylonitrile-based carbon fiber, a special plasticizer is added and the preparation process is improved accordingly, so that the prepared carbon fiber has a good structural orientation, the tensile strength of the carbon fiber is improved, and the application range of the polyacrylonitrile-based carbon fiber is expanded. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Carbon fiber has excellent electrical conductivity, chemical stability, heat resistance and large specific surface area, and has been widely used in various fields such as fuel cells, rail transportation, wind power generation, etc. Despite its widespread application, the mechanical properties of currently prepared carbon fiber, especially its tensile strength, are far from the theoretical value, which seriously hinders its wider commercial application.

[0004] In the production process of carbon fiber, drawing is a crucial step, which helps to optimize the microstructure of the fiber and improve its final mechanical properties. By applying appropriate thermal drawing to PAN fibers, a denser fiber matrix can be obtained and the formation of defective structures can be reduced. However, due to the strong hydrogen bonds and dipole interactions between PAN molecular chains, these intermolecular forces limit their relative sliding, thus posing a challenge to the drawing process of the precursor fibers. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-performance polyacrylonitrile-based carbon fiber and a preparation method thereof. By adding a special plasticizer to improve the fiber's drawability, the graphite structure of the obtained carbon fiber is improved, and the tensile strength is significantly improved, which is expected to pave the way for its wider application.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing high-performance polyacrylonitrile-based carbon fiber, comprising the following steps:

[0008] The polyacrylonitrile, solvent and plasticizer are mixed in proportion, heated and stirred to obtain a uniform spinning solution; the plasticizer is diphenyl phthalate, bisphenol A-bis(diphenyl) phosphate or resorcinol bis(diphenyl) phosphate;

[0009] Spinning the spinning solution to prepare a polyacrylonitrile fiber precursor;

[0010] After the polyacrylonitrile fiber precursor is subjected to heat drawing treatment, it is pre-oxidized and carbonized to obtain polyacrylonitrile-based carbon fiber;

[0011] The pre-oxidation temperature is 200-300°C, and the pre-oxidation time is 80-160 minutes.

[0012] The inventors found in the experiment that plasticizers can weaken the interaction between molecular chains and facilitate the drafting process. Therefore, adding a suitable plasticizer to the PAN precursor is expected to enhance the fiber's draftability. However, commonly used plasticizers have poor heat resistance and are easily decomposed at high temperatures during the carbonization process, resulting in the formation of defective structures in the fiber matrix and reducing the mechanical properties of carbon fibers.

[0013] In the present invention, during the preparation process of polyacrylonitrile carbon fiber, plasticizers such as diphenyl phthalate, bisphenol A-bis(diphenyl) phosphate or resorcinol bis(diphenyl) phosphate are added to the spinning solution to promote the cross-linking of linear PAN molecular chains to form graphite carbon layers during the pre-oxidation and carbonization of the fiber, ultimately leading to improved structure and performance of the carbon fiber.

[0014] Further experiments revealed that when the fiber precursor was pre-oxidized and then carbonized, the mechanical properties of the prepared carbon fiber were better.

[0015] In some embodiments, the solvent is one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide or sodium thiocyanate.

[0016] Preferably, the solvent is dimethylformamide, and the plasticizer is resorcinol bis(diphenyl) phosphate.

[0017] When the solvent is dimethylformamide and the plasticizer is resorcinol bis(diphenyl) phosphate, the drafting performance of the polyacrylonitrile fiber precursor is better and the mechanical properties of the prepared carbon fiber are the best.

[0018] In some embodiments, the solid content of the spinning solution is 13 wt%-25 wt%.

[0019] Preferably, the mass of the plasticizer is 0.01-60 wt % of the mass of the polyacrylonitrile.

[0020] More preferably, the mass of the plasticizer is 1-60 wt % of the mass of the polyacrylonitrile.

[0021] More preferably, the mass of the plasticizer is 10-50 wt % of the mass of the polyacrylonitrile.

[0022] In some embodiments, the spinning is one of electrospinning, wet spinning, dry-jet wet spinning, melt spinning or gel spinning.

[0023] The electrospinning conditions are: temperature 40°C, voltage 20KV, liquid supply rate 2.5ml / h, and take-up roller speed 1000rpm; the dry-wet spinning conditions are: air layer thickness 4-12mm, coagulation bath is an aqueous solution of the solvent used in the spinning solution, temperature 5-25°C, concentration 10-60%. The PAN primary fiber obtained from the coagulation bath is then washed and drawn to obtain PAN raw fiber.

[0024] In some embodiments, the temperature of the heat drawing is 70-160° C.; the actual drawing ratio is 1-10.

[0025] Preferably, the temperature of the hot stretching is 100-160°C; the actual stretching multiple is 3-8.

[0026] More preferably, the temperature of the hot stretching is 120-150° C.; the actual stretching ratio is 3-6.

[0027] In some embodiments, the carbonization is performed under nitrogen or argon conditions at a carbonization temperature of 400-2000°C.

[0028] In a second aspect, the present invention provides a high-performance polyacrylonitrile-based carbon fiber prepared by the preparation method.

[0029] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0030] The carbon fiber preparation method of the present invention can effectively improve the spinnability and stretchability of PAN fibers. The addition of special plasticizers can weaken the van der Waals force between molecules. Under the action of thermal stretching, the fiber molecular chains containing plasticizers are more likely to move along the fiber axis, which helps to reduce the fiber fineness and improve the structural orientation.

[0031] The carbon fiber preparation method of the present invention can promote the improvement of the crystallinity and graphitization degree of the carbon fiber, thereby enhancing the mechanical properties of the fiber. Since the molecular chains are arranged more closely, the fiber porosity is reduced, and the increase in the graphitization degree leads to an increase in the diffusion energy of microcracks. Therefore, compared with the carbon fiber prepared from pure PAN, the tensile strength and modulus of the carbon fiber with the addition of plasticizer are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0033] Figure 1 The SEM morphology of the fiber precursors obtained in Comparative Example 1 and Example 1 of the present invention after heat drawing. Figure a is the PAN fiber image of Comparative Example 1, and Figure b is the fiber image of Example 1 with the addition of plasticizer;

[0034] Figure 2 The figures are the physical pictures of the electrospun fiber membranes obtained after heat drawing in Comparative Example 1 and Example 1 of the present invention, wherein a is the PAN fiber membrane prepared in Comparative Example 1, and figure b is the fiber membrane prepared after adding a plasticizer in Example 1;

[0035] Figure 3 The stress-strain curve (a) and tensile strength comparison diagram (b) of the carbon fibers obtained in Comparative Example 1 and Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Example 1

[0039] A PAN solution with a mass fraction of 19 wt% was prepared using dimethylformamide as solvent, to which a plasticizer, resorcinol bis(diphenyl) phosphate RDP, was added in an amount of 40 wt% of PAN. The obtained spinning solution was poured into a needle tube equipped with a spinning needle with an inner diameter of 0.5 mm, and electrospun at a temperature of 40°C and an electric field strength of 20 kV, and the nanofiber sample was collected by a collection roller with a rotation speed of 1000 rpm.

[0040] The electrospun nanofiber mat was cut along the orientation and subjected to heat drawing treatment in an oven at 135°C with a drawing factor of 4. The fiber mat was then pre-oxidized at 280°C in an air atmosphere and carbonized at 1400°C in a nitrogen atmosphere.

[0041] The tensile strength and modulus of the prepared carbon fiber were measured using a tensile testing machine. The steps are as follows: the carbonized fiber film is divided into strips (30mm x 1mm) along the fiber winding direction, the sample is fixed in a paper frame, and then the breaking strength and Young's modulus are measured by a tensile tester, the effective clamping distance is 20mm, the tensile rate is 5mm / min, and each sample is tested at least 10 times.

[0042] The tensile strength of the prepared carbon fiber is 10.78 MPa and the modulus is 3.25%.

[0043] Example 2

[0044] A PAN solution with a mass fraction of 25 wt% was prepared using dimethylacetamide as solvent, wherein a plasticizer diphenyl phthalate was added in an amount of 20 wt% of PAN. The obtained spinning solution was poured into a needle tube equipped with a spinning needle with an inner diameter of 0.5 mm, and electrospun at a temperature of 40°C and an electric field strength of 20 kV, and the nanofiber sample was collected by a collection roller with a rotation speed of 1000 rpm.

[0045] The electrospun nanofiber mat was cut along the orientation and subjected to heat drawing treatment in an oven at 105° C. The drawing ratio was 6, and then the fiber mat was pre-oxidized at 270° C. in an air atmosphere and carbonized at 1200° C. in an argon atmosphere.

[0046] The tensile strength of the prepared carbon fiber is 6.02 MPa and the modulus is 1.75%.

[0047] Example 3

[0048] A PAN solution with a mass fraction of 13 wt% was prepared using sodium thiocyanate as a solvent, wherein a plasticizer bisphenol A-bis(diphenyl) phosphate was added in an amount of 60 wt% of PAN. The obtained spinning solution was deaerated and then PAN precursor was prepared by dry-jet wet spinning process. After being ejected, the fiber first passed through an 8 mm air layer and then entered a 15° C. coagulation bath, in which the coagulation bath liquid was a 40% dimethyl sulfoxide aqueous solution. After the coagulation bath, the PAN precursor was obtained by multi-stage water washing and hot drawing, and the drawing temperature was 160° C. and the total drawing multiple was 8.

[0049] The drawn raw yarn was pre-oxidized at 300°C in an air atmosphere and carbonized at 2000°C in a nitrogen atmosphere.

[0050] The tensile strength of the prepared carbon fiber is 4.30 MPa and the modulus is 2.18%.

[0051] Example 4

[0052] A PAN solution with a mass fraction of 18 wt% was prepared using dimethyl sulfoxide as a solvent, wherein a plasticizer, resorcinol bis(diphenyl) phosphate, was added in an amount of 5 wt% of the mass of PAN. The obtained spinning solution was degassed and then PAN precursor was prepared using a dry-jet wet spinning process. After the fiber was ejected, it first passed through a 4 mm air layer and then entered a 5°C coagulation bath, in which the coagulation bath liquid was a 20% dimethyl sulfoxide aqueous solution. After the coagulation bath, the PAN precursor was obtained by multi-stage water washing and hot drawing, the drawing temperature was 70°C, and the total drawing multiple was 10 times.

[0053] The drawn raw yarn was pre-oxidized at 200°C in an air atmosphere and carbonized at 450°C in a nitrogen atmosphere.

[0054] The tensile strength of the prepared carbon fiber is 5.98 MPa and the modulus is 1.61%.

[0055] Example 5

[0056] A PAN solution with a mass fraction of 25 wt% was prepared using sodium thiocyanate as a solvent, to which a composite plasticizer of diphenyl phthalate and bisphenol A-bis(diphenyl) phosphate was added. In the composite plasticizer, the mass ratio of diphenyl phthalate to bisphenol A-bis(diphenyl) phosphate was 1:3, and the addition amount thereof was 20 wt% of PAN.

[0057] The obtained spinning solution was poured into a needle tube equipped with a spinning needle with an inner diameter of 0.5 mm. Electrospinning was performed at a temperature of 40° C. and an electric field strength of 20 kV. The nanofiber samples were collected by a collection roller with a rotation speed of 1000 rpm.

[0058] The electrospun nanofiber mat was cut along the orientation and subjected to heat drawing treatment in an oven at 105° C. The drawing ratio was 6, and then the fiber mat was pre-oxidized at 270° C. in an air atmosphere and carbonized at 1200° C. in an argon atmosphere.

[0059] The tensile strength of the prepared carbon fiber is 5.48 MPa and the modulus is 1.39%.

[0060] Example 6

[0061] A PAN solution with a mass fraction of 25 wt% was prepared using dimethylformamide as a solvent, to which a composite plasticizer of diphenyl phthalate and bisphenol A-bis(diphenyl) phosphate was added. In the composite plasticizer, the mass ratio of diphenyl phthalate to bisphenol A-bis(diphenyl) phosphate was 1:3, and the addition amount thereof was 20 wt% of PAN.

[0062] The obtained spinning solution was poured into a needle tube equipped with a spinning needle with an inner diameter of 0.5 mm. Electrospinning was performed at a temperature of 40° C. and an electric field strength of 20 kV. The nanofiber samples were collected by a collection roller with a rotation speed of 1000 rpm.

[0063] The electrospun nanofiber mat was cut along the orientation and subjected to heat drawing treatment in an oven at 105° C. The drawing ratio was 6, and then the fiber mat was pre-oxidized at 270° C. in an air atmosphere and carbonized at 1200° C. in an argon atmosphere.

[0064] The tensile strength of the prepared carbon fiber is 6.44 MPa and the modulus is 1.98%.

[0065] Comparative Example 1

[0066] A PAN solution with a mass fraction of 19 wt% was prepared using dimethylformamide as solvent without adding plasticizer. The obtained spinning solution was poured into a needle tube equipped with a spinning needle with an inner diameter of 0.5 mm, and electrospun at a temperature of 40°C and an electric field strength of 20 kV, and the nanofiber sample was collected by a collection roller with a rotation speed of 1000 rpm.

[0067] The electrospun nanofiber mat was cut along the orientation and subjected to heat drawing treatment in an oven at 135° C. The drawing ratio was 4, and then the fiber mat was pre-oxidized at 280° C. in an air atmosphere and carbonized at 1400° C. in a nitrogen atmosphere.

[0068] like Figure 1 As shown, after the sample to which the plasticizer is added in Example 1 is stretched, the fiber diameter is reduced and the orientation is more obvious, indicating that the addition of the plasticizer improves the stretchability of the fiber.

[0069] Figure 2 The actual pictures are of the electrospun fiber membranes obtained after heat stretching in Comparative Example 1 and Example 1 of the present invention. After stretching, the fiber felt of the sample with plasticizer added in Example 1 is significantly elongated compared with the fiber felt in Comparative Example 1, indicating that the addition of plasticizer improves the stretching performance of the sample.

[0070] Figure 3 This is a comparison diagram of the stress-strain curve and tensile strength of the carbon fibers obtained in Comparative Example 1 and Example 1 of the present invention. It can be seen that the tensile strength of the carbon fibers prepared in Example 1 is significantly greater than that of the carbon fibers prepared in Comparative Example 1.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that the plasticizer resorcinol bis(diphenyl) phosphate is replaced by dipentaerythritol ester, and the rest is the same as Example 1.

[0073] The tensile strength of the prepared carbon fiber is 5.24 MPa and the modulus is 1.74%.

[0074] Comparative Example 3

[0075] The difference from Example 1 is that the pre-oxidation step is omitted, and the rest is the same as Example 1.

[0076] The tensile strength of the prepared carbon fiber is 4.70 MPa and the modulus is 1.29%.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high-performance polyacrylonitrile-based carbon fiber, characterized in that: The steps include: The polyacrylonitrile, solvent and plasticizer are mixed in proportion, heated and stirred to obtain a uniform spinning solution; the plasticizer is diphenyl phthalate, bisphenol A-bis(diphenyl) phosphate or resorcinol bis(diphenyl) phosphate; Spinning the spinning solution to prepare a polyacrylonitrile fiber precursor; After the polyacrylonitrile fiber precursor is subjected to heat drawing treatment, it is pre-oxidized and carbonized to obtain polyacrylonitrile-based carbon fiber; The pre-oxidation temperature is 200-300°C, and the pre-oxidation time is 80-160 minutes.

2. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The solvent is one of dimethylformamide, dimethylacetamide, dimethyl sulfoxide or sodium thiocyanate; Preferably, the solvent is dimethylformamide, and the plasticizer is resorcinol bis(diphenyl) phosphate.

3. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The solid content of the spinning solution is 13wt%-25wt%.

4. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The mass of the plasticizer is 0.01-60wt% of the mass of the polyacrylonitrile; Preferably, the mass of the plasticizer is 1-60wt% of the mass of the polyacrylonitrile; Preferably, the mass of the plasticizer is 10-50 wt % of the mass of the polyacrylonitrile.

5. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The spinning is one of electrostatic spinning, wet spinning, dry-jet wet spinning, melt spinning or gel spinning.

6. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The temperature of hot stretching is 70-160℃; the actual stretching multiple is 1-10.

7. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The temperature of hot stretching is 100-160℃; the actual stretching multiple is 3-8.

8. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 7, characterized in that: The temperature of hot drawing is 120-150℃; the actual drawing multiple is 3-6.

9. The method for preparing high-performance polyacrylonitrile-based carbon fiber according to claim 1, characterized in that: The carbonization is carried out under nitrogen or argon conditions, and the carbonization temperature is 400-2000°C.

10. A high-performance polyacrylonitrile-based carbon fiber, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of grapheme-modified acrylonitrile base carbon fiber

    CN102534870A

  • PAN-based carbon fiber and preparation method thereof

    CN112760752A

  • Coarse-denier high-strength medium-modulus polyacrylonitrile-based carbon fiber and preparation method thereof

    CN112877813A

  • Preparation method of polyacrylonitrile-based carbon fiber and prepared polyacrylonitrile-based carbon fiber

    CN115707806A

  • Polymer porous membrane as well as preparation method and application thereof

    CN118063838A

Cited By

  • Polyacrylonitrile spinning solution, polyacrylonitrile-based carbon fiber as well as preparation and application of polyacrylonitrile-based carbon fiber

    CN121407245A

  • Phosphorus-doped high-performance ternary polyacrylonitrile precursor as well as preparation method and application thereof

    CN121519189A